ChemInform Abstract: 1, 4‐Hydroiodination of Dienyl Alcohols with TMSI to Form Homoallylic Alcohols Containing a Multisubstituted Z‐Alkene and Application to Prins Cyclization. Issue 34 (August 2015) - Xu, Yongjin; Yin, Zhiping; Lin, Xinglong; Gan, Zubao; He, Yanyang; Gao, Lu; Song, Zhenlei
Abstract A new regioselective 1, 4‐hydroiodination of dienyl alcohols is developed using trimethylsilyl iodide as Lewis acid and iodide source.